Prognostic value of transient pattern visual evoked potentials in children with cerebral visual impairment. (28th November 2021) - Howes, Jessica; Thompson, Dorothy; Liasis, Alki; Oluonye, Ngozi; Dale, Naomi; Bowman, Richard
Abstract : Aim: To investigate whether pattern reversal visual evoked potentials (PRVEPs) could predict future visual acuity in infants with cerebral visual impairment (CVI). Method: Fifty‐five children (27 males, 28 females) with severe CVI seen in the ophthalmology department of a specialist children's hospital were identified retrospectively. Behavioural visual acuity and visual evoked potentials (VEPs) at presentation (time 1, T1) were compared with final visual acuity at late preschool/early school age (time 2, T2). Predictors of visual acuity at T2 were identified using univariate and multivariate logistic and linear regression analysis. Results: Median age was 14 months at T1 (range: 6–44mo) and 63 months at T2 (range: 29–150mo). The presence of a PRVEP produced by a check width of 50′ (minutes of arc) or smaller (T1) predicted ( p =0.05) the presence of measurable preferential looking acuity at T2. The presence of PRVEP to check widths of 25′ or smaller (T1) predicted ( p =0.02) better preferential looking acuity (logMAR‐equivalent) scores at T2. The latter association was independent of presenting acuity at T1. Interpretation: The presence of PRVEPs to check widths of 50′ and 25′ in infancy provided useful information. VEPs in young children with CVI may have prognostic value regarding future acuity.